2021
DOI: 10.1111/jac.12481
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress affects floral morphology, silique set and seed quality in chamber and field grown winter canola

Abstract: Canola (Brassica napus L.), also known as oilseed rape or double-low rapeseed, is currently one of the most productive and important oilseed crops grown worldwide (Zhang & Flottmann, 2016). The increasing threat of climate change is already having a substantial impact on agricultural production worldwide, as heat waves can cause significant yield losses (Gornall et al., 2010). Over the past century, global mean air temperature has increased by 0.5°C which is predicted to further increase by 1.5-4.5°C by 2100 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…However, Elferjani and Soolanayakanahally (2018) reported a decrease in the oleic acid content and increased linoleic acid and the saturated fatty acid fraction due to heat stress. Increased saturated (palmitic and stearic) fatty acids without significant changes in unsaturated fatty acids (oleic, linoleic, linolenic) in B. napus in response to high night temperature reported by Pokharel et al (2021). Overall, our results and…”
Section: Short Heat Stress Episode Alters Seed Oil Content and Fatty ...supporting
confidence: 72%
See 3 more Smart Citations
“…However, Elferjani and Soolanayakanahally (2018) reported a decrease in the oleic acid content and increased linoleic acid and the saturated fatty acid fraction due to heat stress. Increased saturated (palmitic and stearic) fatty acids without significant changes in unsaturated fatty acids (oleic, linoleic, linolenic) in B. napus in response to high night temperature reported by Pokharel et al (2021). Overall, our results and…”
Section: Short Heat Stress Episode Alters Seed Oil Content and Fatty ...supporting
confidence: 72%
“…We observed lighter in colour shrunken and irregularly shaped seeds in heat‐stressed plants. Previous studies have also reported that heat stress during flowering in Brassica species results in yield loss exclusively due to a reduction in seed mass potentially due to reduced seed filling duration or increased rate of seed filling (Aksouh‐Harradj et al., 2006; Chen et al., 2021; Gan et al., 2004; Morrison & Stewart, 2002; Pokharel et al., 2021; Rashid et al., 2018; Young et al., 2004; Yu et al., 2014). Our findings indicate that seeds failed to mature properly in some pods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studied fields are no significantly prone to weeds infestation and the rapeseed cultivars authorized in France show generally little phenotypic variability. Nevertheless, [65] also demonstrated the high phenotypic plasticity of rapeseed under short heat stress. Such a plasticity that can possibly occurs under other type of stress or agricultural practices, could also partly explain the absence of correlation between total aboveground dry mass and rapeseed yields observed in this study.…”
Section: Possibility Of Seed Yield Retrieval From Dry Mass Estimationsmentioning
confidence: 96%